Моделі аналізу логічних функцій - Животинський, А. С. (ХНУРЕ, 2023)
The model of xor-relationships for digital circuits îs considered, which allows to solve the problems of technical diagnostics, generative machine leaming, search for similarities-differences between processes and phenomena. The advantages of a vector universal model for a compact description of processes, phenomena, functions and structures are determined.